What motivates academics toward entrepreneurship? Examining the formation of academic entrepreneurial intention from the push-pull perspective - Yu, Zhaoyuan; Lu, Kangyin (Frontiers in Psychology, 2023)
Although academic entrepreneurship has received considerable attention over the last decades, little attention has been devoted to discussing the formation process of academic entrepreneurial intention underlying the push-pull perspective. This study attempts to explore the mechanism of how academic entrepreneurial intention is shaped, with job-related negative elements as push factors, and entrepreneurship-related positive attractors as pull factors. Findings were derived from 1042 academics from Chinese universities. Results showed that both push and pull factors do contribute to boosting academic entrepreneurial intention. Particularly, the entrepreneurship-related pull factors including entrepreneurial opportunity identification and expected entrepreneurial beneﬁts play a dominant role in trigging academic intention to engaging entrepreneurship. Moreover, our findings further confirmed the moderating role of social network in the process of academics pushed by negative job-related factors to emerge entrepreneurial intention. However, social network was not proven to be a moderator in the process of entrepreneurship-related pull factors influencing academic entrepreneurial intention. The findings of the current research provide some important theoretical and practical implications.